Design and Fabrication of Smart Traffic Signal Using Arduino Card - Sura Nuri; Sara M. Mahmood; Omar A. Abdulrazzaq; Ahmed A. Abdullah (Iraqi Journal of Industrial Research, 2022)
Traffic jam is becoming a headache in the big cities all over the world, which causes a significant delay for drivers and passengers. A smart on/off traffic signal optimization based on a motion IR Sensor (Infrared) is now a necessity to overcome this problem. This work is a design and implementation of a smart traffic signal (STS) that controls the time of the traffic signals (Red–Yellow–Green) according to the traffic congestion on the road. The STS is designed to imitate a side road (with a low traffic move) with a highway road (with a high traffic move). A motion IR sensor along with an Arduino PIC were installed to automatically control the traffic signals on/off delay times based on the existence of the vehicles on the side road. When the side road is empty, the highway traffic signal is always green (highway–always–on mode). However, when a vehicle reaches the traffic signal in the side road, the motion IR sensor sends a signal to the Arduino card, so that the highway traffic signal turns red, while the side road traffic signal turns green letting the vehicle to pass the intersection. The system will then automatically set back to the highway–always–on mode. The entire system is designed and simulated using Proteus workbench.